Esophageal Crohn's Disease Treated “Topically” with Swallowed Aerosolized Budesonide - Petros Zezos; Georgios Kouklakis; Anastasia Oikonomou; Michail Pitiakoudis; Constantinos Simopoulos (Case Reports in Medicine)
Proximal Crohn's disease, involving the esophagus, the stomach, the duodenum, and the proximal jejunum, is uncommon. Treatment for proximal Crohn's disease is based on data derived from case series than from controlled trials. We present a case of Crohn's colitis with concomitant proximal esophagogastroduodenal involvement treated with conventional treatment plus swallowed aerosolized budesonide as a novel adjuvant topical treatment for the esophageal disease, and we review the treatment options for proximal Crohn's disease.